الجدار القاتل وآثاره السلبية على الشعب الفلسطيني" "اجتماعياً، نفسياً، صحياً، تعليمياً وحضارياً" دراسة في إطار القانون الدولي العام - الدويك, موسى (revue mofakir; No 12 (2015): مجلـــة المفكــر, 2018)
Since its establishment, Israel has persisted in using hideous violations of international law to terrorize the Palestinian people, to drive them off their land so as to realize the Zionist motto of "A land without people for a people without land". In so doing, it committed massacres, confiscated land colonizing it with settlements and settlers. One of its means to achieve this aim was to begin to construct the racial segregation wall in 2002 on the Occupied Palestinian Territory (OPT). This has had a dire impact on the Palestinian civilians and people in the following aspects: health, psychological well-being, social fabric, education, of Palestinian cultural heritage.